Tuberculosis ganglionar con afectación cutánea (escrofulodermia) en paciente inmunocompetente. Reporte de un caso - Martinez Braga Gabriela; Di Martino Ortiz Beatriz; Rodriguez Masi Mirtha; Knopfelmacher Oilda; Bolla de Lezcano Lourdes (Our Dermatology Online, 2011)
Tuberculosis (TB) infection is most prevalent in the world and its frequency continues to increase, being endemic in Paraguay. TB disease is defined by the presence of clinical symptoms and signs depending on the location of the disease. The most common primary site is the lung. But there are other less common locations such as pleural, pericardial, lymph nodes, miliary, meningeal, osteoarticular, gastrointestinal, renal, pancreatic, breast, skin, eye and genitourinary tract.We report the case of a 21 years old male patient, immunocompetent, with extrapulmonary tuberculosis (lymph node) with secondary skin involvement (scrofuloderma).